Trade Deficit Dilemma: Assessing AIFTA’s Impact on India’s ‎Bilateral Trade - Kanwar, Deepali; Indapurkar, Dr Kavita (International Journal of Accounting and Economics Studies, 2025)
The study examines the AIFTA agreement’s impact on bilateral trade volumes and deficits, implying that one may find that the agreement has a ‎disproportionately positive impact on the ASEAN member states. The study employs a mixed-method approach to analyze structural changes-‎es in India’s trade basket during the AIFTA period. It consists of a product-level analysis at the HS six-digit level for selected liberalized ‎goods, along with a comparative study of MFN and FTA tariff rates to determine their impact on bilateral trade. The study highlights unequal FTA-MFN tariffs for palm oil and pepper, and an inverted duty regime for aluminum and copper, thus emphasizing the need to go ‎deeper and carry out product-level analysis beyond trade deficit trends. Limited access to detailed preferential trade data restricts the ability ‎of AIFTA to carry out empirical analysis. Further research will require more advanced datasets and deeper product-level analysis to adequately track its impact. The study contributes to the AIFTA literature by developing tariff analysis methods and performing case studies to ‎create policy insights that would help in better tariff design under the Agreement‎.